Le jardin-œuvre, une autre façon d’appréhender le jardin collectif autour du travail de l’artiste Emmanuel Louisgrand - Camille Prunet (In Situ)
This article looks at the community gardens created by the French artist Emmanuel Louisgrand, either at his own initiative or at the request of various associations, institutions or communities. Conceived as artworks, these gardens offer spaces for meetings and exchanges in derelict public places in urban contexts. Artistic legacies such as those of Joseph Beuys or the Arte povera movement are important in Louisgrand’s gardens, designed as manifestos offering social and creative spaces. Examples are to be found in French cities like Lyons, Caen and Saint-Étienne and also several cities abroad. The question of recognising these collective-gardens-cum-works-of-art as heritage is particularly delicate since it raises the issue of conserving the garden with all its living and growing elements whilst also preserving the collective dynamics that sustain it. How does an artwork aim at rethinking the role of the community garden by focusing not so much on the control of the living as on its symbolic function? Through the example of Emmanuel Louisgrand’s artworks, our article seeks to analyse the issues surrounding community gardens today and the difficulties raised by their recognition as heritage.